2001
DOI: 10.1084/jem.194.2.189
|View full text |Cite
|
Sign up to set email alerts
|

Defective Gp130-Mediated Signal Transducer and Activator of Transcription (Stat) Signaling Results in Degenerative Joint Disease, Gastrointestinal Ulceration, and Failure of Uterine Implantation

Abstract: The receptor subunit gp130 transduces multiple cell type–specific activities of the leukemia inhibitory factor (LIF)/interleukin (IL)-6 family of cytokines through the signal transducer and activator of transcription (STAT) and src homology 2 domain–bearing protein tyrosine phosphatase (SHP)-2/ras/Erk pathways. To define STAT-dependent physiological responses, we generated mice with a COOH-terminal gp130ΔSTAT “knock-in” mutation which deleted all STAT-binding sites. gp130ΔSTAT mice phenocopyed mice deficient f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
129
1
2

Year Published

2003
2003
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 217 publications
(137 citation statements)
references
References 48 publications
(99 reference statements)
4
129
1
2
Order By: Relevance
“…These pathways could also be involved in RA (38). Future studies should address their induction by IL-6 and the interplay between these different pathways in arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…These pathways could also be involved in RA (38). Future studies should address their induction by IL-6 and the interplay between these different pathways in arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…26,39 In contrast, mice with a mutation selectively abrogating only SHP-2-Ras-ERK (MAPK) signaling (gp130 757F ) were resistant to colitis, but developed gastric adenomas as a consequence of unopposed STAT3 signaling. 26,39 A conclusion of these detailed Figure 8. Immunohistochemical staining for TFF3 protein in mouse liver at 12 weeks after BDL showed expression was exclusively limited to the large bile ducts and peribiliary glands (inset) in IL-6 ϩ/ϩ mouse liver (A), but weakly present in the large bile ducts in IL-6 Ϫ/Ϫ (B) mouse liver.…”
Section: Discussionmentioning
confidence: 99%
“…15,16,28,42 Trefoil peptides also enhance intestinal epithelial restitution primarily by stimulating epithelial cell spreading and migration, which accelerates mucosal epithelial recovery after injury. 40,43 Each of the TFF proteins is differentially regulated in different parts of the gastrointestinal tract: 26,39 TFF1 and TFF2 are expressed primarily in the stomach 44,45 and TFF3 predominates in the small and large intestines. 41 In the liver, this and previous studies have shown that TFF1 and TFF3 are constitutively expressed in the large bile ducts of mouse and human livers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is now clear that lymphoid and nonlymphoid cell types express a functional IL-27R (i.e., WSX-1 and gp130), and that the functions of this dimeric receptor are not restricted to the regulation of T cell activity. The recognition that gp130, a receptor chain that has been linked to the suppression of inflammation (44,45), forms part of the IL-27R complex supports an inhibitory role for IL-27. Thus, IL-27/IL-27R interactions may provide a general mechanism to down-regulate immune activity in multiple hemopoietic cell types.…”
Section: Discussionmentioning
confidence: 99%